Influence of composition of ß-TCP and borate bioglass scaffolds on cell proliferation of adipose tissue-derived mesenchymal stem cells: osteogenic differentiation (2021)
Scaffolds with Schwarz D geometry based on triply periodic minimal surfaces (TPMS) were obtained by 3D printing with a biodegradable and bioactive paste (66.5% calcium phosphate with and without magnesium, 28.5% bioglass borate (BGBS), 3% attapulgite, and 2% water by weight). The osteogenic differentiation of mesenchymal stem cells (hMSC) was performed from human adipose tissue (ADSCs) in the presence of the scaffolds, which were characterized by degradability (International Organization for Standar ISO 10993—Part: 14), in vitro bioactivity by immersion tests in SBF arranged by Kokubo at different time intervals, cell proliferation, and osteogenic differentiation by alkaline phosphatase activity. Calcium phosphate is associated with β-tricalcium phosphate (β-TCP), in addition to amorphous Bioglass Borate. Scaffolds with calcium and magnesium phosphate (β-TCP/Mg) showed better degradability and bioactivity than scaffolds without Mg. Both scaffolds showed porosity and pore interconnectivity. Mesenchymal stem cells showed good adhesion and cell proliferation in contact with the scaffolds. Scaffolds doped with Mg were better promoters of cellular proliferation, additionally they did not show a cytotoxic effect. Differentiation of the osteogenic environment was verified by alkaline phosphatase activity.